Species identification of Malayan Gaur, Kedah-Kelantan and Bali cattle using polymerase chain reaction-restricted fragment length polymorphism - Mohd Nor, Siti Romaino; Zainal Abidin, Fazly Ann; Loo, Shu San; Mail, Mohd Hafiz; Darus, Mohamad Hafiz; Ismail, Mohd Iswadi; Kashiani, Pedram; Rosli, Muhammad Khairul Anwar; Syed Shabthar, Syed Mohamad Fahmi; Md Zain, Badrul Munir; Othman, Abas Mazni (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2014)
Mitochondrial DNA (mtDNA) is a useful genetic marker that can be used for species identification. The cytochrome b (Cyt b) gene is a suitable mtDNA candidate gene for use in phylogenetic analyses due to its sequence variability, which makes it appropriate for comparisons at the subspecies, species, and genus levels. This study was conducted to develop a rapid molecular method for species identification of Malayan gaur (Bos gaurus hubbacki), Kedah-Kelantan (KK) (Bos indicus), and Bali (Bos javanicus) cattle in Malaysia. DNA was extracted from blood samples of 8 Malayan gaurs, 30 KK, and 28 Bali cattle. A set of both specific and universal primers for the Cyt b gene were used in PCR amplification. DNA sequences obtained were then analyzed using BioEdit and Restriction Mapper softwares. The PCR products obtained from Cyt b gene amplification were then subjected to restriction enzyme digestion. The amplification, using both specific and universal primers, produced a 154- and a 603-bp fragment, respectively, in all three species. Two restriction enzymes, NlaIV and SspI, were used to obtain specific restriction profiles that allowed direct identification of Malayan gaur, KK, and Bali cattle. Our findings indicate that all three species can be identified separately using a combination of universal primers and the restriction enzyme SspI.